Religion Identity And Political Polarization: How Does Labeling Make It Worst? - Nahrul Hayat; Nurhakki Nurhakki (Institut Agama Islam Negeri Palopo, 2022)
Prabowo's joining of President Jokowi's cabinet is expected to end the polarization of tadpoles versus